Abuse Of Power And The Right Of Inviolability By Foreign Diplomats (A Case Study Of Espionage By The Australian Ambassador Against Indonesia In 2013) - Denda Retno Pirdayanti; Muh. Risnain; Diva Pitaloka (Mataram Journal of International Law, 2024)
This research aims to analyze the abuse of diplomatic power by foreign diplomats, focusing on the case of Australian espionage against Indonesia in 2013. It evaluates the impact of this espionage on diplomatic relations, trust between the two nations, and the legal implications under international law, including state responsibility. This study employs normative legal research methods, combining document analysis, case studies, and a review of international legal literature. The findings highlight violations of international law, a deterioration in diplomatic relations, and a decline in trust. It underscores the need for fair enforcement of laws addressing breaches of diplomatic immunity. This research emphasizes the principles of international law, the responsibility of states for unlawful actions by diplomats, and the importance of strict oversight to uphold the integrity of diplomatic relations.